Perancangan dan Implementasi Video Media Pembelajaran Produk Kreatif Dan Kewirausahaan di SMKN 2 Batam Menggunakan MDLC - Madani umpu nikan; Diny Anggriani Adnas (Publikasi Indonesia, 2022)
The development of the industry that is not in sync with the provision of sufficient human resources, especially for the management and tourism industries, causes the need for human resources in these fields to increase. SMK Negeri 2 Batam is a public school established in 2006 with